Comparative life cycle assessment of deinking sludge utilization alternatives. (20th January 2016) - Deviatkin, Ivan; Kapustina, Viktoriia; Vasilieva, Elena; Isyanov, Lev; Horttanainen, Mika
Abstract: The aim of this research was to quantify and compare the environmental impact of a number of different deinking sludge utilization approaches. A comparative life cycle assessment of deinking sludge material and energy recovery was performed for the baseline scenario—landfill disposal, and four alternative scenarios: two cement plants, a lightweight aggregate plant, and a stone wool plant. Sludge pretreatment and transportation processes were included in the scenario analyses. The results of the life cycle assessment showed that the use of dry deinking sludge in a cement plant in Finland, 45 km from the point of supply of the deinking sludge, to substitute 46% of the petcoke and 2.7% of the limestone showed the best performance. Therein, a global warming potential reduction of 13% and an eutrophication potential reduction of 12% – the highest reduction out of all impact categories studied – were achieved. A similar reduction in global warming potential of 12% was achieved when deinking sludge was incinerated and the ash utilized in cement production in a Russian plant located 350 km from the paper mill. However, abiotic depletion potential and acidification potential slightly increased by 2.6 and 1.5%, respectively. A maximum reduction of 2.1% out of al impact categories was achieved when dry sludge was used in a lightweight aggregate plant. That is considerably less compared to the reduction achieved at the cement plants. The use of deinking sludge ash in a stone wool plant to substitute 25% of cement resulted in a maximum reduction of 25% in the ozone layer depletion potential. Thus, the utilization of deinking sludge in construction materials production while preventing its landfilling has beneficial effects on the environment, in particular decreased greenhouse gas emissions. Highlights: 4 + 1 deinking sludge management approaches were compared in the study. Attributional life cycle assessment with system expansion was applied. Utilization of deinking sludge for petcoke substitution showed best performance. All alternative scenarios resulted in reduced GWP. Fuels substitution exerts greater effect on results than raw materials.